AirQMon: Indoor Air Quality Monitoring System Based on Microcontroller, Android and IoT - Jacquline Waworundeng; Walfarid Hermawan Limbong (CogITo Smart Journal, 2020)
Humans were often unaware of the risk of contaminated indoor air quality. Based on this, the researcher designs an Indoor Air Quality Monitoring System based on Arduino which could help to raise the human awareness of air quality. This research is based on the Prototyping method. The system hardware built with Arduino Uno which connected to MQ135 sensor to monitor the air quality and Sound Buzzer to sound an alarm whenever the sensor sensed the air quality in a risky value. The Ethernet Shield is used to connect the Arduino Uno to the internet, which enables the process to upload the data which has been read by the sensor to an IoT platform called ThingSpeak. The air quality data which uploaded to ThingSpeak, then retrieved by AirQmon, a customized Android application developed by the researcher to monitor the air quality which is installed on the smartphone. The data is presented graphically to the user through AirQmon apps. This system results in a form of a device and application which could potentially be used as a monitoring system and raise human awareness of indoor air quality.